Searching for the public: school funding and shifting meanings of 'the public' in Australian education. Issue 4 (4th July 2017) - Gerrard, Jessica; Savage, Glenn C.; O'Connor, Kate
Abstract: School funding is a principal site of policy reform and contestation in the context of broad global shifts towards private- and market-based funding models. These shifts are transforming not only how schools are funded but also the meanings and practices of public education: that is, shifts in what is 'public' about schooling. In this paper, we examine the ways in which different articulations of 'the public' are brought to bear in contemporary debates surrounding school funding. Taking the Australian Review of Funding for Schooling (the Gonski Report) as our case, we analyse the policy report and its subsequent media coverage to consider what meanings are made concerning the 'publicness' of schooling. Our analysis reveals three broad themes of debate in the report and related media coverage: (1) the primacy of 'procedural politics' (i.e. the political imperatives and processes associated with public policy negotiations in the Australian federation); (2) changing relations between what is considered public and private; and (3) a connection of government schooling to concerns surrounding equity and a 'public in need'. We suggest these three themes contour the debates and understandings that surround the 'publicness' of education generally, and school funding more specifically.